Correlation between the serum neutralization test and the indirect immunofluorescent test for the detection of specific antibodies to infectious bovine rhinotracheitis virus. - Assaf, R (1975)
Comparative titrations show that immunofluorescence on infected rabbit kidney cells is relatively as sensitive as the neutralization test for the detection of antibodies to the infectious bovine rhinotracheitis virus. When calf testis cells infected with this virus are used for the detection of antibodies by the indirect immunofluorescent test nonspecific staining is high. This nonspecific reaction is absent when rabbit kidney cells are used.